A multi‐layer, closed‐loop system for continuous measurement of soil CO2 concentration. Issue 1 (31st August 2017) - Jochheim, Hubert; Wirth, Stephan; von Unold, Georg
Abstract: We present a setup of measurement devices that allow the continuous measurement of CO2 concentrations at different soil depths using small nondispersive infrared (NDIR) sensors within a 16‐channel closed‐loop system. Hydrophobic, gas‐permeable polypropylene membrane tubes allow an equilibrium of CO2 concentration of circulating air, driven by peristaltic pumps, with soil air. The advantage of this system over other systems is the option to measure up to 16 channels without a time shift between individual measurements, as occurs when using a multiplexer system. Furthermore, the system prevents carry‐over effects. A 16‐position multiplexer provides a connection to an isotopic CO2 analyzer for measurement campaigns. This approach aimed to detect vertical concentration profiles and temporal variation of soil CO2 concentration and δ 13 C‐CO2 signature in soils and to determine the impact of underlying environmental drivers based on concurrent measurements of soil temperature and moisture. The system was tested by applying it in a beech and a pine forest stand during a period of 15 d. Soil CO2 concentrations were mostly determined by soil temperature as well as by soil moisture at a biweekly scale. At diel scale, the dynamic of soil CO2 concentrations followed the shape of soil temperature, sometimes with some time shift. The observed values of δ 13 C‐CO2 at 10–30 cm soil depths ranged between –22.0 and –19.0‰ at the beech site and –22.4 and –21.8‰ at the pine site, with a distinct vertical gradient at the beech site. Our results show that the system is reliable in practical application, capable of continuously detecting soil CO2 concentrations and its isotopic signature (δ 13 C‐CO2 ) with high temporal resolution.